PENGARUH DIGITAL MARKETING: SOCIAL MEDIA CAMPAIGN TERHADAP MINAT MENDAFTAR DI PERGURUAN TINGGI (STUDY KASUS: UNIVERSITAS GLOBAL JAKARTA) - Hertin, Revita Desi; Ahmad Pitra (Jurnal Sosial Humaniora dan Pendidikan, 2024)
Technological developments in the modern era are currently increasing and spreading widely. These technological changes also have an impact on the business in Indonesia, including the world of marketing. From brand awareness, sales and transactions, everything has been done digitally. In the Education Sector, some of the problems currently faced by universities are in the marketing process, several marketing methods must be maximized because their benefits are enormous. Choosing the type of advertising, market targeting that does not match the target market (consumers) makes the use of social media marketing work not optimally and goes over budget. Marketing content such as the use of catchy words, promotions, image quality and product information are part of this marketing content. The number of Enrolled students each year will have an impact on University Sustainability. The aim of this research is to analyze the impact of digital marketing, especially social media campaigns in higher education institutions on the New Student Admissions process. A quantitative research approach was used in this research as the method used, through questionnaires as a data collection method. The results of this research show that there is a positive relationship between the variables tested. Based on the results of data analysis, the variables Targeting Socio Economy, Distance and marketing content have a positive effect on digital marketing performance and have a positive effect on University Sustainability. In future research, it is hoped that other researchers will be able to highlight other variables or use different targets such as MSMEs.